FAO fisheries technical paper; N389 - Stefania Vannuccini (FAO, 1999)
The book details the species used and the methods of preservation for the various purposes. It assembles information, as well as the latest statistical available, from those parts of the world where sharks are important economically as a sustantial fisheries sector, a contribution to human food or a valuable trading them.